Effective Mosquito Repellents: Myrcene- and Cymene-Loaded Nanohydrogels against Aedes aegypti - Duarte, Jonatas Lobato [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Ribeiro, Tais de Cássia [UNESP]; Silva, Ana Carolina de Jesus; Hage-Melim, Lorane Izabel da Silva; Duchon, Stéphane; Carrasco, David; Pinto, Mara Cristina [UNESP]; Corbel, Vincent; Chorilli, Marlus [UNESP] (MDPI, 2024)
Aedes mosquito-borne diseases remain a significant global health threat, necessitating effective control strategies. This study introduces monoterpenes-based nanohydrogels for potential use as repellents against Aedes aegypti, the primary dengue vector worldwide. We formulated hydrogels using cymene- and myrcene-based nanoemulsions with different polymers: chitosan, carboxymethylcellulose (CMC), and carbopol®. Our evaluations of rheological, texture, and bioadhesive properties identified CMC hydrogel as the most promising gelling agent for topical application, exhibiting sustained monoterpene release over 12 h with low skin permeation and high retention in the stratum corneum. Myrcene-loaded CMC hydrogel achieved a 57% feeding deterrence compared to 47% with cymene hydrogel in the mosquito membrane-feeding model. Molecular docking studies revealed interactions between myrcene and an essential amino acid (Ile116) in the Ae. aegypti odorant-binding protein 22 (AeOBP22), corroborating its higher repellent efficacy. These findings suggest that myrcene-loaded CMC hydrogels offer a promising, minimally invasive strategy for personal protection against Ae. aegypti and warrant further investigation to optimize monoterpene concentrations for vector control.
Keywords: arboviruses; carboxymethylcellulose; cymene; myrcene; nanoemulsion